Improving Academic Performance by Applying Total Quality Management Tools: A case of Bangladeshi Students - Rahim, Mir Abdur; Utsha, Auvishek Modak; Bhuiyan, Ishtiaq Ahmed; Miah, Md. Rakib; Haque, Md. Raquibul (Curriculum and Educational Technology Department, 2018)
This article describes the educational practice of engineering student in Bangladesh, especially how they are still practicing the old and conventional way of learning, mainly by memorizing the entire subject they learn and push them to answer the question exactly as written in the book. This phenomenon brings the student to fxate on the book and will inhibit their creativity and innovation notions, even though without considering the eﬀort to hone the students’ creativity and innovation domain, the knowledge will not develop properly, including in engineering. Trough this research the total quality management (TQM) had been developed to lead the students to get a better and satisfying result of study without losing the eﬀort to develop their creativity, innovation and research skills as important factor and main purpose of engineering education. Abstrak  Artikel ini menggambarkan praktik pendidikan di Bangladesh, terutama pada mahasiswa teknik yang masih belajar menggunakan pendekatan konvensional, yakni belajar dengan menghafal materi dari buku dan mengikuti ujian dengan cara menjawab persis seperti yang tertulis di buku. Hal tersebut menjadikan siswa terlalu terpaku pada buku hingga kesulitan untuk mengembangkan kreativitas dan inovasi mereka. Padahal tanpa memperhatikan pentingnya upaya untuk mengasah kreativitas dan inovasi, ilmu pengetahuan tidak akan berkembang, termasuk dalam bidang teknik. Melalui penelitian ini, pendekatan total quality management telah dikembangkan untuk mengarahkan siswa-siswa memperoleh hasil studi yang memuaskan selain juga tetap diarahkan untuk mengembangkan kreativitas, inovasi, keterampilan riset dan lainnya yang sejatinya juga merupakan tujuan utama pendidikan teknik. Keywords: Academic performance; creativity; engineering; innovation; memorizing; total quality management